An estimation of educational production function: the case of Tasmanian public schools - Mohd. Arshad, Mohd. Nahar (2010)

(untitled)
The purpose of this study is to investigate the effects of school resources on students’ academic achievement. The underlying theoretical framework of the study posits education as a production process, where an educational production function based on individual-level panel data of students in Tasmania is estimated. Evidence has been found on the positive effects of educational expenditure per student and rural expenditure to school on students’ academic achievement. Evidence also has been found to support a policy to reduce student-teacher ratio. The findings of the study stand as a crucial source of insight to a more informed debate over education policy in Tasmania.